Peranan BUMP dalam Meningkatkan Kemandirian Ekonomi Pesantren dalam Perspektif Ekonomi Syariah (Studi Kasus: Pesantren Syekh Hasan Yamani) - Abdul Malik; Nasra; Busrah (DPPM Universitas Pelita Bangsa, 2025)
Currently, pesantrens are still dependent on donors and external assistance, so efforts are needed to achieve economic independence in order for pesantrens to be financially self-sufficient and sustainable. The purpose of this study is to examine the role of the Pesantren-Owned Enterprises (BUMP) in managing pesantren economic ventures to create a stable source of income and reduce dependence on external parties. The research method used is qualitative, with data collection through observation, interviews, and documentation. The results show that BUMP contributes significantly to improving the welfare of the pesantren and its students, as well as serving as an entrepreneurship learning medium for the students. With the existence of BUMP, the pesantren can carry out its functions of education, da'wah, and community empowerment more independently in economic terms. In conclusion, the existence of Pesantren-Owned Enterprises is a strategic step in realizing the economic independence of pesantrens, with professional management and optimal utilization of local potential.